The influence of job training, compensation and work environment on employee performance - Risaldy Amry; Ledy Lutfiani Jamilah; Nevi Sulistiawati Afriani; Wahid Sumarjo; Wahyudi Wahyudi; Ahmad Solihin (Junal Ilmu Manajemen, 2026)
This study was carried out to examine how job training, employee compensation, and the work environment influence the performance of employees at Horison Ultima Ratu Serang Hotel. Although previous studies have widely examined the effects of job training, compensation, and the work environment on employee performance, the findings remain inconsistent, particularly within the hospitality industry in developing economies. This study addresses this gap by providing empirical evidence from the Indonesian hotel industry and examining the combined effects of job training, compensation, and the work environment on employee performance. A quantitative approach using descriptive and explanatory methods was employed with a saturated sample of 87 employees. Data were collected through questionnaires and analyzed using SPSS, including validity, reliability, classical assumption, multiple regression, coefficient of determination, and hypothesis tests. The results indicate that job training, compensation, and the work environment each have a positive and significant effect on employee performance. Furthermore, the work environment had a positive and significant impact on employee performance, indicating that comfortable and supportive workplace conditions help employees perform more effectively. At the same time, it was shown that job training, pay, and working conditions significantly affect how well employees perform, accounting for 54% of the differences in their performance levels. These findings highlight the importance of improving employee competencies through training, providing equitable compensation, and fostering a supportive work environment to enhance employee performance in the hospitality industry. The study contributes to human resource management theory by reinforcing the complementary role of human resource development, reward systems, and workplace conditions as integrated determinants of employee performance, while offering practical guidance for hotel managers in designing more effective human resource strategies.